Effects of pore-water pH and calcium concentration on the microstructure of kaolin. Issue 1 (2nd December 2019) - Capotosto, A.; Russo, G.
Abstract : A multi-scale analysis on the effects of pore-water chemistry on the microstructure of a clayey soil is presented in this paper. Pore-water chemistry affects the interaction between clay particles regulating surface charge distribution and determining their aggregation. For the experimental study, non-active clay (Speswhite TM kaolin) samples prepared with different pore-water chemistry have been reconstituted to highlight the interaction and aggregation between particles. Microstructural features of particles aggregation were investigated by means of mercury intrusion porosimetry and scanning electron microscopy. Microstructural analyses show two main pore classes induced by pore-water chemistry characterising the pore-size distributions of samples. The role of aggregation on mechanical behaviour has then been investigated on treated samples subjected to one-dimensional consolidation at different stress levels. Microstructural analyses highlighted fabric modifications induced by loading paths for each initial aggregation.